Multiple testing: when is many too much?. Issue 3 (March 2021) - Groenwold, Rolf H H; Goeman, Jelle J; Cessie, Saskia Le; Dekkers, Olaf M
Abstract : In almost all medical research, more than a single hypothesis is being tested or more than a single relation is being estimated. Testing multiple hypotheses increases the risk of drawing a false-positive conclusion. We briefly discuss this phenomenon, which is often called multiple testing. Also, methods to mitigate the risk of false-positive conclusions are discussed.